Assessment of Beliefs, Behaviors and Opinion About Blood Donation in Etawah District, Uttar Pradesh, India : A cross sectional study - Kumar, Anshul; Kumar, Sandip; Raheja, Lokesh; Maurya, Adarsh; Verma, Anurag; Binwal, Shivani (Indian Journal of Community Health, 2025)
Background: Blood donation is a critical component of modern healthcare, saving millions of lives annually worldwide. Despite its importance, many regions—including rural areas in India—face a chronic shortage of blood supplies. Factors such as socio-demographic characteristics, cultural beliefs, awareness, and motivation all influence the willingness to donate blood. Community-based studies help in understanding population-level perspectives and barriers to voluntary blood donation in specific settings. Aim & Objective: To assess the beliefs, behaviors, and opinions of the public towards blood donation. Settings and Design: In Etawah, this community-based cross-sectional survey conducted between June and August 2022. Material& Method: Technique of random sampling was applied. Employing a semi-structured questionnaire, data has been collected. Result: 87.6% of participants thought that blood donation may save lives, and majority (82.6%) thought it was an essential act. A total of 27.8% of participants were willing to give blood voluntarily, and 35.4% of participants accepted receiving blood from voluntary donors. Conclusion: The participant's motivation, beliefs, and opinions toward blood donation were positive. The majority of them also thought that giving blood may save lives and that it was a significant action.